Generation of a Dynamic System of Three‐Dimensional Tetrahedral Polycatenanes1. Issue 22 (18th April 2013) - Black, Samuel P.; Stefankiewicz, Artur R.; Smulders, Maarten M. J.; Sattler, Dominik; Schalley, Christoph A.; Nitschke, Jonathan R.; Sanders, Jeremy K. M.
<x xml:space="preserve">Abstract</x> Seven of the best: A dynamic combinatorial library of polycatenated tetrahedra was prepared by complexation between a dynamic Fe4L6 tetrahedral cage, constructed from ligands containing an electron‐deficient naphthalenediimide core, and an electron‐rich aromatic crown ether, 1, 5‐dinaphtho[38]crown‐10. The highest order species in the library is the tetrahedral [7]catenane.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>